Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1680/macr.2010.62.11.831
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of adhesive-based self-healing of cementitious materials

Abstract: This paper presents the results of a series of self-healing experiments conducted on reinforced mortar beams containing adhesive-filled glass reservoirs. An overview of the findings of the preliminary investigation stage of experiments is given in addition to the results of a parametric study which investigates the effect of the level of reinforcement and loading rate on the amount of self-healing. Results show that both primary and secondary healing occurs during the first and second loading cycles respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
109
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(114 citation statements)
references
References 8 publications
4
109
0
1
Order By: Relevance
“…Indeed the glass tubing approach may be considered a variant of chemical encapsulation as an alternative form of healing agent delivery approach, with the advantage of potentially carrying a larger amount of healing agent compared with microcapsules. Various chemicals including methyl methacrylate (Dry and McMillan 1996), ethyl cyanoacrylate (Li et al 1998;Joseph et al 2010) and polyurethane combined with an accelerator (van Tittelboom et al 2011) have demonstrated the ability of recovering concrete mechanical and transport properties. These chemicals are chosen to have low viscosity so that the healing agents can leak from the fractured glass tube into the concrete crack to perform the self-healing.…”
Section: Self-healing Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed the glass tubing approach may be considered a variant of chemical encapsulation as an alternative form of healing agent delivery approach, with the advantage of potentially carrying a larger amount of healing agent compared with microcapsules. Various chemicals including methyl methacrylate (Dry and McMillan 1996), ethyl cyanoacrylate (Li et al 1998;Joseph et al 2010) and polyurethane combined with an accelerator (van Tittelboom et al 2011) have demonstrated the ability of recovering concrete mechanical and transport properties. These chemicals are chosen to have low viscosity so that the healing agents can leak from the fractured glass tube into the concrete crack to perform the self-healing.…”
Section: Self-healing Approachesmentioning
confidence: 99%
“…As noted above, the healing agent is not limited to chemicals, but could be biological (Wang et al 2012). Evidence of self-healing was based on mechanical reloading of beam elements that show a rebound of stiffness and/or strength (Li et al 1998;Joseph et al 2010;Van Tittelboom et al 2011) and a reduction of permeability coefficient (Van Tittelboom et al 2011).…”
Section: Self-healing Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many self-healing approaches, including autogenous, adhesive-based, mineral admixtures-based, and bacteriabased methods, have been developed [7]. There are two mechanisms for self-healing in concrete such as autonomous healing and autogenous healing [10][11][12]. Autogenous healing is a natural process which heals small cracks depending upon the composition of the concrete.…”
Section: Introductionmentioning
confidence: 99%
“…On parle alors de « cicatrisation autonome ». Ainsi, divers agents cicatrisants, majoritairement de nature chimique, ont été dé-veloppés et appliqués avec succès dans les matériaux cimentaires [1,13,14]. Plus récemment, la possibilité d'utiliser un agent cicatrisant d'origine biologique a été considérée [15][16][17][18].…”
unclassified